Human sexual dimorphism: from an evolutionary perspective to practical . overview - Suriyanto, Rusyad Adi (Universitas Gadjah Mada, 2009)
This paper goal is to discuss human sexual dimorphism in evolutionary perspective and practical overview. Evolution of human sexual dimorphism has wide implication !n human biological study and many applications to medical field. Human sexual dimorphism has experienced changes and adaptations along its proceeding to current time and space. These changes are natural consequences. Understanding this problem as process and products of evolution, we can enter this problem into medicine and be a background. Understanding as a background, as human natural history, we will understand why human can be so now and why he! she will change, including sexual dimorphism problem. The understanding of background is needed to avoid creation of human with narrow vision, highly specialized, excessive fanatics for self competency, easily astonished, panic and immediately tricked in real life which is complex and continuously changing. Human anatomy knowledge, as one basic medical aspect, sexually presents understanding that there are changing and developing characteristics among men (males) and women (femalesl over time. The medical intentions are aspects of sexual dimorphism directly applied and related closely to medicine. The paper begins with sexual dimorphism discussion, and continued by evolutionary perspective discussion, and followed up by practical discourse. This continuity is an effort to illustrate that Homo sapiens species, like us, is always dynamic and changing, like nature which is never static neither stable.